Legume germination is delayed in dry soils and in sterile soils devoid of microbial mutualists: Species‐specific implications for upward range expansions. Issue 8 (23rd August 2022) - Keeler, Andrea M.; Rafferty, Nicole E.
Abstract: Climate change is affecting species and their mutualists and can lead to the weakening or loss of important interspecific interactions. Through independent shifts in partner phenology and distribution, climatic stress can separate mutualists temporally or spatially, leading to alterations in partner functional traits and fitness. Here, we explored the effects of the loss of microbial mutualists on legume germination success and phenology. In particular, we assessed the effects of mutualism loss via soil sterilization, increased drought, and introduction to novel soils found beyond the current distributions of two focal legume species in subalpine environments. Through common garden experiments in controlled environments, we found evidence that soil sterilization (and consequent microbial absence) and dry soils caused species‐specific phenological delays of 2–5 weeks in germination, likely as a result of interaction loss between legumes and specialized germination‐promoting soil microbes, such as mutualistic rhizobia. Delays in germination caused by a mismatch between legumes and beneficial microbes could negatively affect legume fitness through increased plant–plant competition later in the season. Additionally, we found evidence of the presence of beneficial microbes beyond the current elevational range of one of our focal legumes, which may allow for expansion of the leading edge, although harsh abiotic factors in the alpine may hinder this. Alterations in the strength of soil microbe‐legume mutualisms may lead to reduced fitness and altered demography for both soil microbes and legumes. Abstract : In this article, we assess the effects of mutualism loss via soil sterilization, drought, or introduction to novel soils found beyond the current distributions of two focal legume species in subalpine environments. Through common garden experiments in controlled environments, we find evidence that soil sterilization (and consequent microbial absence) and dry soils cause phenological delays of 2‐5 weeks in germination date, likely as a result of interaction loss between legumes and germination‐promoting soil microbes, such as mutualistic rhizobia.